2010
DOI: 10.1111/j.1440-1746.2009.06144.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of polygenetic polymorphisms on the susceptibility to non‐alcoholic fatty liver disease of Chinese people

Abstract: Background and Aim: The aim of this study was to investigate the influence of polygenetic polymorphisms, which play a role in the pathogenesis of metabolic syndrome, on the susceptibility to non-alcoholic fatty liver disease (NAFLD) of Chinese people. Methods: The subjects were selected from an epidemiological survey in the Guangdong province of southern China. In each polymorphism study, 50-117 subjects who met the diagnostic criteria of NAFLD and had typical clinical and ultrasonographic findings were placed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
79
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(88 citation statements)
references
References 23 publications
(54 reference statements)
6
79
0
3
Order By: Relevance
“…In line with these results, increased levels of TNFa were observed in patients with steatohepatitis compared with healthy subjects (Hui et al 2004). Moreover, it has been established that certain TNFa polymorphisms increase the susceptibility to NAFLD (Zhou et al 2010). Taken together, these results indicate that TNFa may be an adapted therapeutic target to treat NAFLD.…”
Section: Tumor Necrosis Factor Asupporting
confidence: 76%
See 1 more Smart Citation
“…In line with these results, increased levels of TNFa were observed in patients with steatohepatitis compared with healthy subjects (Hui et al 2004). Moreover, it has been established that certain TNFa polymorphisms increase the susceptibility to NAFLD (Zhou et al 2010). Taken together, these results indicate that TNFa may be an adapted therapeutic target to treat NAFLD.…”
Section: Tumor Necrosis Factor Asupporting
confidence: 76%
“…Therefore, several controversies remain to be clarified regarding the pathological role of TNFa in NAFLD. Xu et al (2002) TNFa is present in white adipose tissue and its production is significantly increased in different rodent obesity models Arner (2003) TNFa level correlates with insulin resistance Hotamisligil (2003) Blocking TNFa with an antibody increases insulin sensitivity Uysal et al (1997) Mice lacking TNFa function are protected against obesity-induced insulin resistance Meyer & de Groot (2003) TNFa induces cytotoxicity through regulation of ceramide synthesis Tilg & Diehl (2000) Increased TNFa level in NAFLD patients Lesmana et al (2009) Correlation between TNFa and degree of liver fibrosis in NAFLD subjects Zhou et al (2010) High prevalence of certain TNFa polymorphisms in patients with NAFLD Lee et al (2008) Pharmacological inhibition of TNFa reduces aminotransferase levels in patients with NAFLD IL6 Bastard et al (2002) IL6 produced by white adipose tissue contributes to insulin resistance observed in obese humans El-Assal et al (2004) IL6 protects against ethanol-induced liver injury Wallenius et al (2002) IL6-deficient mice develop mature onset obesity and associated insulin resistance Wieckowska et al (2008) Hepatic IL6 expression correlates with the severity of NAFLD Yamaguchi et al (2010) Blocking IL6 prevents liver damage and enhances liver steatosis In summary, metabolic alterations leading to lipid accumulation promotes local TNFa production (e.g. liver) and kinase activation.…”
Section: Tumor Necrosis Factor Amentioning
confidence: 99%
“…Forty-five studies were identified by electronic and manual searches, 15 of which were selected for full-text review based on title and abstract details (Butt et al, 2006;El-Sohemy et al, 2006;Terauchi, 2007;Hui et al, 2008;Pan et al, 2009;Dongiovanni et al, 2010;Gupta et al, 2010;Rey et al, 2010;Zhou et al, 2010;Cao et al, 2012;Bowes et al, 2012;Gawrieh et al, 2012;Yang et al, 2012;Bhatt et al, 2013;Jalil et al, 2013). Six studies were excluded because one contained no data (Gawrieh et al, 2012), two had other polymorphism data (Hui et al, 2008;Zhou et al, 2010), and three had a genotype distribution in controls that was not in HWE (Gupta et al, 2010;Bhatt et al, 2013;Jalil et al, 2013).…”
Section: Studies Included In the Meta-analysismentioning
confidence: 99%
“…This is consistent with previous reports in which the adiponectin G/G genotype is associated with non-alcoholic fatty liver disease (NAFLD) (Tokushige el al. 2009) and that the subjects with T allele of adiponectin G+276T polymorphism have a decreased risk of non-alcoholic steatohepatitis (NASH) in Chinese people (Zhou et al 2010). Interestingly, the group consisting of the subjects with TNF-α 857T allele and adiponectin +276G/G genotype (Group 3), had the highest proportion of subjects with a liver/spleen CT ratio < 0.9, which is a marker of fatty liver (Saitoh et al 1988;Park et al 2006), although there was no significant difference in the liver enzyme levels such as AST, ALT and γ-GTP, relating to fatty liver (Table 2 and 5).…”
Section: Homa-ir (N)mentioning
confidence: 99%
“…It has been reported that adiponectin gene polymorphisms such as G+276T in intron 2 are associated with higher serum concentrations of adiponectin (Hara et al 2002;Matsuzawa 2010;Katakami et al 2011). The adiponectin +276T allele is associated with a decreased risk of non-alcoholic steatohepatitis (NASH) (Zhou et al 2010), whereas the G/G genotype is associated with obesity, risk of type 2 diabetes, cardiovascular diseases (Hara et al 2002;Matsuzawa 2010;Katakami et al 2011) and non-alcoholic fatty liver disease (NAFLD) (Tokushige el al. 2009).…”
mentioning
confidence: 99%